Vers une grammaticalisation de the way : une alternative au binôme conjonctif as / like - Mathilde Pinson (Corela)
The choice between the comparative conjunctions as and like depends primarily on sociolinguistic and stylistic factors. In the same syntactic slot, speakers can also use the way, although the literature on comparative conjunctions rarely mentions this third possibility. By examining the incomplete NP the way in light of grammaticalization criteria, such as decategorialization, loss of paradigmatic variability, erosion, and semantic bleaching, I demonstrate that the way is becoming a conjunctive phrase. As an intermediate option between as, which is sometimes considered too formal, and like, which is not yet accepted in every situation, the way seems to be more neutral from a sociolinguistic perspective and is therefore central to the grammar of comparative conjunctions.